(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article it is considered legal questions of food security of RK. In article today’s situation, and problems of food security is discussed. And at the end of article it is considered ways a solution ensuring food security. Key words: food safety, subsistence coefficient, food basket.